Evaluation Of The Multi Level Referral System Policy In Health Service Facilities - Mardia Habel; Gunawan Hi Ibra; Liskha Ayuningrum; M Awaluddin; Feby Triadi; Hana Humayrah (Jurnal Pengelolaan Kesehatan Berkelanjutan berbasis Kearifan Lokal, 2025)
Access to equitable health services in Indonesia is supported by a tiered referral system within the National Health Insurance (JKN) program, which regulates service continuity between primary and advanced healthcare facilities. Although this system has expanded service access and reduced financial barriers, its implementation remains challenged by infrastructure limitations, unequal distribution of health workers, weak inter-facility coordination, and low public understanding of referral procedures. This study aimed to evaluate the implementation of the multi-level referral system policy within the JKN framework in Indonesian health service facilities. A structured literature review was conducted using the Google Scholar database. Articles published between 2020 and 2025 were screened and selected using predefined inclusion and exclusion criteria. A total of six eligible studies were analyzed using thematic analysis to identify recurring patterns related to implementation effectiveness, resource availability, coordination mechanisms, and public understanding. The results show that the JKN program has improved access to healthcare services and reduced financial barriers; however, the referral system has not functioned optimally due to disparities in infrastructure, limited human resource capacity, weak coordination between service levels, and insufficient program socialization. The novelty of this study lies in its integrative synthesis of structural, organizational, and behavioral dimensions in evaluating referral system performance. This study provides evidence-based insights to support policy strengthening aimed at improving efficiency, equity, and sustainability of health services and accelerating the achievement of universal health coverage in Indonesia.